Ragam Bahasa Indonesia Tentara Nasional Indonesia Angkatan Darat Kajian Psikolinguistik - Nita Wiryandani, Ni Kadek; Suparwa, I Nyoman; Putu Putra, Anak Agung (Humanis; Vol 23 No 4 (2019), 2019)
This research entitled “Indonesian Language Variety of the Army; Psycholinguistic studies”. The way it expess are also in firm, solid, and clear manner. This research is the background of the author to conduct a research on the diversity of languages applied in the military.  The aims of this research is to describe and understand the use of language in the military. The method used in this study is descriptive qualitative research method, interview techniques, and oral direct communication with students and military teachers. The implication of this study on linguistics knowledge is that on psycholinguistic study, to find out the mentality of a student while studying at Rindam IX/Udayana.